Modelling Improvements in Cell Yield of Banked Umbilical Cord Blood and the Impact on Availability of Donor Units for Transplantation into Adults - Natasha Kekre; Jennifer Philippe; Ranjeeta Mallick; Susan Smith; David Allan (Hindawi Limited, 2013)
Umbilical cord blood (UCB) is used increasingly in allogeneic transplantation. The size of units remains limiting, especially for adult recipients. Whether modest improvements in the yield of cells surviving storage and thawing allow more patients to proceed to transplant was examined. The impact of improved cell yield on the number of available UCB units was simulated using 21 consecutive anonymous searches. The number of suitable UCB units was calculated based on hypothetical recipient weight of 50 kg, 70 kg, and 90 kg and was repeated for a 10%, 20%, and 30% increase in the fraction of cells surviving storage. Increasing the percentage of cells that survive storage by 30% lowered the threshold of cells needed to achieve similar engraftment rates and increased numbers of UCB units available for patients weighing 50 (P=0.011), 70 (P=0.014), and 90 kg (P=0.003), controlling for differences in HLA compatibility. Moreover, if recipients were 90 kg, 12 out of 21 patients had access to at least one UCB unit that met standard criteria, which increased to 19 out of 21 patients (P=0.035) when the fraction of cells surviving storage and thawing increased by 30%. Modest increases in the yield of cells in banked UCB units can significantly increase donor options for adult patients undergoing HSCT.